Emperipolesis is a potential histological hallmark associated with chronic hepatitis B. - Hu, Y.; Jiang, L.; Zhou, G.; Liu, S.; Liu, Y.; Zhang, X.; Zhao, S.; Wu, L.; Yang, M.; Ma, L.; Wang, X.; Zhao, J. (Current Molecular Medicine, 2015)
Although emperipolesis exists in infectious liver diseases, the diagnostic value of emperipolesis in chronic hepatitis B is not exactly known. The aim of this study is to evaluate the histological characteristics and laboratory parameters of emperipolesis in chronic hepatitis B. Totally 402 patients with hepatitis B and other liver diseases were processed in a retrospective assessment. Inflammatory severity of hepatitis B was evaluated with Ishak Scoring System. Immunofluorescent staining was performed for CD8 (T cells), CD20 (B cells), CD56 (NK cells), CD68 (macrophages) and MPO (neutrophils). Emperipolesis was observed in 74.0% of patients with chronic hepatitis B (CHB) and 82.8% of patients with acute hepatitis B (AHB). In emperipolesis, CD8+ T cell was the main cell type. Patients with emperipolesis in CHB got high scores of inflammatory activity. Among patients with CHB, emperipolesis was present with higher serum ALT, AST and GGT levels. HBV DNA Load in patients with emperipolesis was as 10 times high as those without emperipolesis. HBeAb was significantly correlated with the evidence of emperipolesis. In chronic hepatitis B, emperipolesis was associated with severity of liver injury. The presence of emperipolesis was an indicator of active liver inflammation.
Keywords: active liver inflammation